Discovery of a Cell‐Active SuTEx Ligand of Prostaglandin Reductase 2. (29th April 2021) - Toroitich, Emmanuel K.; Ciancone, Anthony M.; Hahm, Heung Sik; Brodowski, Skylar M.; Libby, Adam H.; Hsu, Ku‐Lung
Abstract: Sulfonyl‐triazoles have emerged as a new reactive group for covalent modification of tyrosine sites on proteins through sulfur‐triazole exchange (SuTEx) chemistry. The extent to which this sulfur electrophile can be tuned for developing ligands with cellular activity remains largely underexplored. Here, we performed fragment‐based ligand discovery in live cells to identify SuTEx compounds capable of liganding tyrosine sites on diverse protein targets. We verified our quantitative chemical proteomic findings by demonstrating concentration‐dependent activity of SuTEx ligands, but not inactive counterparts, against recombinant protein targets directly in live cells. Our structure‐activity relationship studies identified the SuTEx ligand HHS‐0701 as a cell‐active inhibitor capable of blocking prostaglandin reductase 2 (PTGR2) biochemical activity. Abstract : A tyrosine‐reactive PTGR2 inhibitor : A cell‐active sulfonyl‐triazole compound (HHS‐0701) that ligands Y100 on prostaglandin reductase 2 (PTGR2) was discovered by quantitative chemical proteomics. Biochemical assays support HHS‐0701 blockade of PTGR2 metabolism of the lipid substrate 15‐Keto‐PGE2 . These findings bolster the potential for developing SuTEx compounds as pharmacological modulators of proteins in live cells.